Reversible Photoswitching of a Spin‐Crossover Molecular Complex in the Solid State at Room Temperature. (7th September 2015) - Rösner, Benedikt; Milek, Magdalena; Witt, Alexander; Gobaut, Benoît; Torelli, Piero; Fink, Rainer H.; Khusniyarov, Marat M.
Abstract Spin‐crossover metal complexes are highly promising magnetic molecular switches for prospective molecule‐based devices. The spin‐crossover molecular photoswitches developed so far operate either at very low temperatures or in the liquid phase, which hinders practical applications. Herein, we present a molecular spin‐crossover iron(II) complex that can be switched between paramagnetic high‐spin and diamagnetic low‐spin states with light at room temperature in the solid state. The reversible photoswitching is induced by alternating irradiation with ultraviolet and visible light and proceeds at the molecular level.